Intervensi Berbasis Edukasi pada Ibu terhadap Feeding Practice Ibu dalam Upaya Peningkatan Status Gizi Anak Stunting pada Usia 6-24 Bulan - Ringgi, Maria Susana Ine Nona; Keuytimu, Yosephina M.H. (Poltekkes Kemenkes Tanjung Karang, 2022)
Stunting increases in Indonesia because the practice of complementary feeding has not met the UNICEF program standards. Nutrition education is one of the recommendations to overcome mothers’ feeding practices. This study aims to influence the educational-based interventions on maternal eating practices in Paga Village. This study was quasi-experimental research designed with one pre-test and post-test group and without a control group. The sample of this study involved 45 respondents selected by a total sampling technique. The feeding practices were measured through a questionnaire. The intervention was given three times. The data were analyzed by employing paired sample t-test. There is an effect of education-based intervention interventions on the feeding practice of companion breast milk (p-value 0.00; T-5.223). Changes in better feeding practice occur by fulfilling points of the feeding practice program. This intervention can be an alternative for health workers to continue to promote and for the mothers to apply for feeding practice programs.